(De)legitimization of single mothers' welfare rights: United States, Britain and Israel. (July 2022) - Herbst-Debby, Anat
This article contributes to the theoretical discussion of the historical legitimacy of single mothers by examining the construction of relationships between single motherhood and welfare policy. Specifically, the study analyses the changing discourse regarding single mothers, and the social policy designed for them, in the US, UK and Israel from the 1970s to the 2000s. These three countries are similar in terms of the embeddedness, extension and institutionalization of neoliberal ideology in their welfare policies and public discourse, together with welfare legislation affecting single mothers, yet they differ in terms of policy implementation and the history of policy development. The study examines institutional intersectionality along with cultural perceptions of single mothers in each country. Looking at both the development and the withdrawal of social rights over time, we deepen understanding of how the image of the single mother is created in the neoliberal welfare regime.